ONLINE VEGETABLE PURCHASE DECISION FOR CONSUMERS IN INDONESIA - Nanang Kusuma Mawardi; Avivah Rahmaningtyas (MANAJEMEN DEWANTARA, 2023)
Currently, exchange activities can be carried out without meeting physically through electronic markets or what is commonly referred to as e-commerce. Research results from merchantmachine.co.uk (2019) stated that e-commerce growth in Indonesia was the fastest in the world at 78%. Currently, there are many types of businesses that use e-commerce as a medium for transactions as well as marketing, including types of businesses that sell fresh products such as vegetables. Data from the 2018 National Socio-Economic Survey (SUSENAS) (in Sumantri, 2019) shows an increase in vegetable consumption in Indonesia in 2015 from 29.68 kcal/capita/day to 37.95 kcal/capita/day in 2018. User growth the internet in Indonesia and the increase in vegetable consumption are good opportunities for online vegetable shops to expand their business. This study aims to determine what factors influence consumers' online vegetable purchasing decisions in Indonesia. The stages of the research method that will be carried out are starting with data collection, both primary data and secondary data. Primary data was obtained by distributing questionnaires to respondents. The questionnaire uses a google form and is distributed online. Research respondents were selected using a non-probability sampling method with an accidental sampling technique. The data processing method is using the Structural Equation Modeling - Partial Least Square (SEM-PLS) model with 5 independent variables and 1 dependent variable. The independent variables in this study are perceived usefulness (PU), perceived convenience (PEOU), attitudes, subjective norms, and perceptions related to behavioral control, while the dependent variable in this study is purchasing decisions. The targeted outputs are the publication of Scopus-indexed international journals and international seminar proceedings. TKT results of this study are expected to be at level 6, namely the achievement of a conclusion from the results of the analysis of consumer behavior who shop for vegetables online. Then a draft recommendation can be drawn up for vegetable marketing actors and the government as a regulator. The results showed that the factors that influence online vegetable purchasing decisions by Indonesian consumers in this study were Perception of Ease (PU), Attitude (AT), and Perception of Behavioral Control (PCB). Factors that have no effect are perceived usefulness and subjective norms. These results illustrate that respondents in this study tend to buy vegetables online when each individual can access internet technology. Respondents also tend to make purchasing decisions based on internal factors because they believe in their ability to carry out activities and have no effect on their external environment.